Pengembangan Aplikasi “Smart Tajwid” Berbasis Android untuk Meningkatkan Motivasi Belajar Tajwid Siswa pada Mata Pelajaran Pendidikan Agama Islam - Nova Aulia Azizah (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2019)
This research and development was carried out to determine the feasibility level of the Smart Tajwid application based on the assessment of the media experts, material experts and PAI teachers, as well as to determine the motivation to learn recitation of students after using the Smart Tajwid application. This study refers to the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. But in the trial application to see an increase in students' motivation to learn recitation, the researcher used this type of experimental research pretest post test control group design. By taking the background of SMP N 1 Polanharjo Klaten class VIII. Data analysis techniques in this study used 2 types of analysis, namely qualitative and quantitative with inferential and descriptive statistical approaches, to process the data obtained using the SPPS 21 application. The validation results of the Smart Tajwid application show the percentage of eligibility based on: 1) media experts at 95.23% , 2) subject matter experts at 91.25%, 3) teachers at 92.85% and 3) students in small group trials at 92.5%. Overall, the Smart Tajwid application developed with a predicate is very suitable to be used as a medium for learning Tajweed. In addition, the application trial to see an increase in students' motivation to learn Tajweed after using the Smart Tajwid application has increased, which is based on the results of the independent sample t-test analysis between the experimental class and the control class having a difference of 3.2812. Then it can be concluded that the increase in motivation to learn recitation of students in the experimental class who get special treatment using the Smart Tajwid application has increased motivation higher than the control class that does not get special treatment. Abstrak Penelitian dan pengembangan ini dilakukan untuk mengetahui tingkat kelayakan aplikasi Smart Tajwid berdasarkan penilaian ahi media, ahli materi dan guru PAI, serta untuk mengetahui motivasi belajar tajwid siswa setelah menggunakan aplikasi Smart Tajwid. Penelitian ini mengacu pada model ADDIE yang terdiri dari 5 tahap yaitu Analysis, Design, Development, Implementation, Evaluation. Namun dalam uji coba aplikasi untuk melihat peningkatan motivasi belajar tajwid siswa, peneliti menggunakan jenis penelitian eksperimen pretest post test control group design. Dengan mengambil latar SMP N 1 Polanharjo Klaten kelas VIII. Teknik analisis data dalam penelitian ini menggunakan 2 jenis analisis yaitu kualitatif dan kuantitatif dengan pendekatan statistik inferensial dan deskriptif, untuk mengolah data yang diperoleh menggunakan aplikasi SPPS 21. Hasil validasi aplikasi Smart Tajwid menunjukkan presentase kelayakan berdasarkan: 1) ahli media sebesar 95,23%, 2) ahli materi sebesar 91,25%, 3) guru sebesar 92,85% dan 3) siswa pada uji coba kelompok kecil sebesar 92,5%. Secara keseluruhan aplikasi Smart Tajwid yang dikembangkan berpredikat sangat layak digunakan sebagai media belajar tajwid. Selain itu, dalam uji coba aplikasi untuk melihat peningkatan motivasi belajar tajwid siswa setelah menggunakan aplikasi Smart Tajwid mengalami peningkatan, yaitu berdasarkan hasil analisis uji independent sampel t-test antara kelas eksperimen dengan kelas kontrol mempunyai selisih 3,2812. Maka dapat disimpulkan bahwa peningkatan motivasi belajar tajwid siswa pada kelas eksprimen yang mendapatkan perlakuan khusus menggunakan aplikasi Smart Tajwid mengalami peningkatan motivasi lebih tinggi dibandingkan kelas kontrol yang tidak mendapatkan perlakuan khusus.